INOVASI PEMBELAJARAN PAI DI SEKOLAH PADA ERA DISRUPTIVE INNOVATION - Tedi Priatna (Universitas Islam Negeri (UIN) Mataram, 2018)
The main focus of this paper is the innovative idea of Islamic Education learning in schools facing the disruptive innovation of the digital age. The discussion uses critical analytics as part of the development of descriptive methods. The object of study is ideas. Data collection techniques used are book survey or library research. The results of the discussion show several important findings. (1) Learning model is a conceptual framework that describes the systematic procedure in organizing experiences to achieve learning objectives. The learning model is formed from the element of focus, syntax, social system and learning situation, and supporting factor. (2) Learning Islamic Education is an effort to encourage learners to earn the curriculum of Islamic Education which resulted in a change in the behavior of learners. There are efforts to be taken to optimize the learning of Islamic Education in schools facing disruptive innovation. First, there is a need to change the paradigm of learning Islamic Education not only limited to cognitive orientation, but also psychomotor domain, affection, and attitude aspects as well as religious behavior. Second, Islamic Education learning in schools/madrasah should be developed and innovated in such a way that Islamic Education learning is up-to-date and attracts students’ interest. The use of information technology in the Islamic Education learning model should continue to be developed and placed as a source, reference, and information resource. The use of social media in learning should also be an alternative, including the use and utilization of social media for the development of Islamic Education learning in schools.